Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Correction: The sarcoma ring trial: a case-based analysis of inter-center agreement across 21 German-speaking sarcoma centers (Journal of Cancer Research and Clinical Oncology, (2025), 151, 1, (30), 10.1007/s00432-024-06063-z) - Roohani, Siyer; Handtke, Jolina; Hummedah, Kamal; Albertsmeier, Markus; Andreou, Dimosthenis; Apostolidis, Leonidas; Augustin, Marinela; Bauer, Sebastian; Billner, Moritz; Bösch, Florian; Deinzer, Christoph K.W.; Deventer, Niklas; et al. (Journal of Cancer Research and Clinical Oncology, 2025)
In this article, the author’s name Armin Tuchscherer was incorrectly written as Armin Tuscherer. The original article has been corrected.
CRIS-Team Scopus Importer:2025-05-02

Interdisciplinary Surgical Therapy of Extremity Soft-Tissue Sarcomas: A Personalized Resection and Reconstruction Algorithm - Osterloh, Justus; Ludolph, Ingo; Grützmann, Robert; Meyer, Alexander; Lang, Werner; Horch, Raymund E.; Fechner, Katja; Arkudas, Andreas (Journal of Personalized Medicine, 2023)
Soft-tissue sarcomas (STS) are rare, but potentially life-threatening malignancies. STS can occur anywhere in the human body with the limbs being the most common site. Referral to a specialized sarcoma center is crucial to guarantee prompt and appropriate treatment. STS treatment strategies should be discussed in an interdisciplinary tumor board to involve expertise from all available resources, including an experienced reconstructive surgeon for an optimal outcome. In many cases, extensive resection is needed to achieve R0 resection, resulting in large defects after surgery. Hence, an evaluation of whether plastic reconstruction might be required is mandatory to avoid complications due to insufficient primary wound closure. In this retrospective observational study, we present data of patients with extremity STS treated at the Sarcoma Center, University Hospital Erlangen, in 2021. We found that complications were more frequent in patients who received secondary flap reconstruction after insufficient primary wound closure compared to patients who received primary flap reconstruction. Additionally, we propose an algorithm for an interdisciplinary surgical therapy of soft-tissue sarcomas regarding resection and reconstruction and present two problematic cases to emphasize the complexity of surgical sarcoma therapy.
CRIS-Team Scopus Importer:2023-03-10
Keywords: extremity soft-tissue sarcomas; reconstructive surgery; surgical resection

Long‐term follow‐up of patients receiving neoadjuvant treatment modalties for soft tissue sarcomas of the extremities - Rauch, Miriam; Agaimy, Abbas; Semrau, Sabine; Willner, Alexander; Ott, Oliver; Fietkau, Rainer; Hohenberger, Werner; Croner, Roland S.; Grützmann, Robert; Fechner, Katja; Vassos, Nikolaos (Cancers, 2021)
Background: Neoadjuvant treatment modalities in soft tissue sarcoma (STS) of the extremities have become more popular in recent years, but because of the rarity and heterogeneity of STS, there are yet few studies on the long‐term impact of neoadjuvant treatment modalities, especially in terms of neoadjuvant radiochemotherapy. Methods: The study enrolled 136 patients with primary STS of the extremities who underwent surgery with curative intent or neoadjuvant therapy, followed by surgery in a 15‐year period. Neoadjuvant treatment consisted of radiotherapy (RT) with 60 Gy and in most cases simultaneous chemotherapy (CTx) with ifosfamide (1.5 g/m2/d, d1–5, q28) and doxorubicine (50 mg/m2/d, d3, q28). We investigated the clinical, (post)‐operative and histopathological data and the oncological follow‐up as well. The median follow‐up period was 82 months (range 6–202). Results: A total of 136 patients (M:F = 73:63) with a mean age of 62 years (range; 21–93) was observed. Seventy‐four patients (54.4%) received neoadjuvant therapy (NT), 62 patients (45.6%) received primary surgery (PS). When receiving NT, patients with high‐risk STS had a lower risk to develop distant metastasis (p = 0.025). Age, histological type, tumor size and surgical margins (R0 vs. R1) had no influence on any survival rates. There was an association between NT and the occurrence of postoperative complications (p = 0.001). The 5‐year local recurrence free survival (LRFS), metastasis free survival (MFS), disease free survival (DFS) and overall survival (OS) rate of the whole cohort was 89.9%, 77.0%, 70.6% and 72.6%; whereas the 5‐year LRFS, MFS, DFS and OS rate was 90.5%, 67.2%, 64.1% and 62.8% for the NT group and 89.5%, 88.3%. 78.4% and 83.8% for the PS group. Conclusion: Multimodal treatment strategies in patients with STS of extremities lead to excellent oncological outcomes. Patients with high‐risk STS had a significantly better MFS when receiving NT than patients with low‐risk STS. NT was associated with a higher probability of postoperative but well‐manageable complications.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Extremity; Neoadjuvant therapy; Radiation; Radiochemotherapy; Soft tissue sarcoma

Neoadjuvant concurrent chemoradiotherapy with and without hyperthermia in retroperitoneal sarcomas: feasibility, efficacy, toxicity, and long-term outcome - Willner, Alexander; Fechner, Katja; Agaimy, Abbas; Haller, Florian; Eckstein, Markus; Ott, Oliver; Putz, Florian; Gaipl, Udo; Kersting, S.; Meidenbauer, Norbert; Grützmann, Robert; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2021)
Purpose Retroperitoneal (RPS) sarcomas are associated with poor local and abdominal tumor control. However, the benefit of preoperative radio- or chemotherapy alone for these entities is currently unclear. Moreover, as intermediate- and high-grade sarcomas have a tendency toward early metastasis, exploration of neoadjuvant strategies is of high importance. This analysis reports the results of our 20-year single-institution experience with preoperative neoadjuvant concurrent chemoradiation. Methods From 2000-2019, 27 patients with intermediate- or high-grade RPS (12 dedifferentiated liposarcoma, 10 leiomyosarcoma, 5 others) were treated with radiotherapy (median dose: 50.4 Gy; range 45-75 Gy) and two cycles of chemotherapy (doxorubicin 50 mg/m(2) BSA/d3 q28 and ifosfamide 1.5 g/m(2) BSA/d1-5 q28) in neoadjuvant intent. Chemotherapy consisted of doxorubicin alone in two cases and ifosfamide alone in one case. Fifteen patients (56%) additionally received deep regional hyperthermia. Results The median follow-up time was 53 months (+/- 56.7 months). 92% of patients received two cycles of chemotherapy as planned and 92% underwent surgery. At 5 and 10 years, abdominal-recurrence-free survival was 74.6% (+/- 10.1%) and 66.3% (+/- 11.9%), distant metastasis-free survival was 67.2% (+/- 9.7%) and 59.7% (+/- 11.1%), and overall survival was 60.3% (+/- 10.5%) and 60.3% (+/- 10.5%), respectively. CTC grade III and IV toxicities were leukocytopenia (85%), thrombocytopenia (33%), and anemia (11%). There were no treatment-related deaths. Conclusion Neoadjuvant chemoradiotherapy with and without hyperthermia for retroperitoneal sarcomas is feasible and provided high local control of intermediate- and high-grade sarcoma.
CRIS-Team WoS Importer:2021-11-12

The health-related quality of life of sarcoma patients treated with neoadjuvant versus adjuvant radiotherapy – Results of a multi-center observational study - Singer, Susanne; Semrau, Sabine; Golcher, Henriette; Fechner, Katja; Kallies, Annett; Zapata Bonilla, Sergio; Grützmann, Robert; Fietkau, Rainer; Kluba, Torsten; Jentsch, Christina; Andreou, Dimosthenis; Bornhäuser, Martin; et al. (Radiotherapy and Oncology, 2023)
Aim: The sequence of radiotherapy and resection in patients with soft tissue sarcomas is usually discussed on an individual basis. Better understanding of potential differences of health-related quality of life (QoL) between patients undergoing adjuvant (ART) versus neoadjuvant radiotherapy (NART) is therefore helpful for clinical decision making. Methods: Adult sarcoma patients from 39 hospitals completed the European Organisation for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30). Differences in global QoL, physical functioning, role functioning, fatigue, pain, and insomnia between ART versus NART were investigated with multivariate regression, adjusting for age, gender, chemotherapy, grading, stage, tumor location, recurrence/distant metastasis, sarcoma type, time since last treatment, and treatment status using validated thresholds. Results: A total of 1110 patients participated. Of them, 340 had received radiotherapy (NART: n = 95, 28%; ART: n = 245, 72%). Global QoL was 59.3 on average after NART and 60.5 after ART (Badj = 1.0, p = 0.74). Physical functioning was 65.9 compared to 70.5 (Badj = 4.2; p = 0.16), role function 48.8 vs. 56.7 (Badj = 7.0, p = 0.08), fatigue 47.5 vs. 45.4 (Badj = -1.2; p = 0.71), pain 40.2 vs. 34.1 (Badj = -6.8; p = 0.08), and insomnia 33.7 vs. 41.6 (Badj = 5.5, p = 0.16). Among patients with NART, clinically relevant QoL impairments were less frequent 2 years after treatment compared to < 2 years thereafter (n = 6 vs. n = 4 on average). Conclusion: There is little evidence for QoL differences in most domains and overall QoL between the two irradiation groups. However, patients after NART might experience worse role functioning and pain but fewer problems with insomnia compared to patients after ART.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Leiomyosarcoma; Liposarcoma; Neoadjuvant Therapy; Neoplasms; Connective and Soft Tissue; Patient Reported Outcome Measures; Radiotherapy; Adjuvant

The management of retrorectal tumors – a single-center analysis of 21 cases and overview of the literature - Fechner, Katja; Bittorf, B.; Langheinrich, M.; Weber, K.; Brunner, Maximilian; Grützmann, Robert; Matzel, Klaus (Langenbecks Archives of Surgery, 2024)
Aim: Retrorectal tumors are rare and heterogeneous. They are often asymptomatic or present with nonspecific symptoms, making management challenging. This study examines the diagnosis and treatment of retrorectal tumors. Methods: Between 2002 and 2022, 21 patients with retrorectal tumors were treated in our department. We analyzed patient characteristics, diagnosis and treatment modalities retrospectively. Additionally, a literature review (2002–2023, “retrorectal tumors” and “presacral tumors”, 20 or more cases included) was performed. Results: Of the 21 patients (median age 54 years, 62% female), 17 patients (81%) suffered from benign lesions and 4 (19%) from malignant lesions. Symptoms were mostly nonspecific, with pain being the most common (11/21 (52%)). Diagnosis was incidental in eight cases. Magnetic resonance imaging was performed in 20 (95%) and biopsy was obtained in 10 (48%). Twenty patients underwent surgery, mostly via a posterior approach (14/20 (70%)). At a mean follow-up of 42 months (median 10 months, range 1–166 months), the local recurrence rate was 19%. There was no mortality. Our Pubmed search identified 39 publications. Conclusion: Our data confirms the significant heterogeneity of retrorectal tumors, which poses a challenge to management, especially considering the often nonspecific symptoms. Regarding diagnosis and treatment, our data highlights the importance of MRI and surgical resection. In particular a malignancy rate of almost 20% warrants a surgical resection in case of the findings of a retrorectal tumour. A local recurrence rate of 19% supports the need for follow up.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Presacral mass; Retrorectal tumors; Tailgut cyst; Treatment

The sarcoma ring trial: a case-based analysis of inter-center agreement across 21 German-speaking sarcoma centers - Roohani, Siyer; Handtke, Jolina; Hummedah, Kamal; Albertsmeier, Markus; Andreou, Dimosthenis; Apostolidis, Leonidas; Augustin, Marinela; Bauer, Sebastian; Billner, Moritz; Bösch, Florian; Deinzer, Christoph K.W.; Deventer, Niklas; et al. (Journal of Cancer Research and Clinical Oncology, 2025)
Purpose: The management of soft tissue sarcoma (STS) at reference centers with specialized multidisciplinary tumor boards (MTB) improves patient survival. The German Cancer Society (DKG) certifies sarcoma centers in German-speaking countries, promoting high standards of care. This study investigated the variability in treatment recommendations for localized STS across different German-speaking tertiary sarcoma centers. Methods: In this cross-sectional case-based survey study, 5 anonymized patient cases with imaging data of localized STS were presented to MTBs of 21 German-speaking tertiary referral hospitals. Centers provided recommendations on treatment sequence and modalities, along with the consensus level within their MTB. Agreement percentages were calculated, and consensus levels were rated on a scale of 1 to 10. Results: Five patient cases were discussed resulting in 105 recommendations. Agreement percentages for case 1 to 5 were 14.3%, 61.9%, 33.3%, 52.4% and 9.3%, with a median agreement percentage of 33.3%. Grouping pre- and postoperative therapies as "perioperative" and including recommendations with and without regional hyperthermia raised the median agreement to 47.6%. The mean consensus level within each center across all 5 cases was 9.5. Conclusion: This first case-based analysis of inter-center agreement for STS management in German-speaking countries reveals low inter-center agreement but high intra-center consensus. Our study includes nearly all tertiary sarcoma centers in German-speaking countries, affirming its strong external validity. These findings suggest potential and clinically very relevant differences in treatment standards among sarcoma centers. Enhanced case-based exchanges and collaborative efforts are needed to reduce discrepancies and standardize the management of STS patients.
CRIS-Team Scopus Importer:2025-01-31
Keywords: German Cancer Society; Guidelines; Inter-center agreement; Reference center; Ring trial; Soft tissue sarcoma